Клинический случай повторного эндодонтического лечения хронического апикального периодонтита зубов 4.7 и 4.8 у пациента 73 лет (LLC "Endo Press", 2020)
In this paper we consider the case of treatment of chronic periodontitis in a patient of 73 years. After the examination the diagnosis was «chronic apical periodontitis of teeth 4.7 and 4.8». The treatment plan was agreed with the patient. The entire course of treatment is described. A positive result after three years of treatment was confirmed radiographically.